A Study of the Effect of a Protein on the Structure of Water in Solution Using Terahertz Time-Domain Spectroscopy. Issue 2 (February 2018) - Penkov, Nikita; Yashin, Valery; Fesenko, Eugeny; Manokhin, Andrew; Fesenko, Eugeny
Terahertz time-domain spectroscopy (THz-TDS) was used to determine the spectra (range = 1.2–120 cm −1 ) of aqueous solutions of bovine serum albumin (BSA) at pH range 2.5–10. Under each of the selected pH, BSA molecules exist in a different conformation, compared to other pH values. The spectra were used to calculate the functions of the dielectric permittivity of BSA solutions. Dielectric functions of the aqueous phase of BSA solutions were calculated based on the Bruggeman model, without the contribution of BSA itself. Fitting of the dielectric functions was performed using a model which includes three water spectral bands: two relaxation bands with relaxation times of about 8.28 and 0.3 ps and a vibrational band with a maximum of about 180 cm −1 . The parameters of these bands were determined through fitting and physical interpretation at the molecular level can be provided for each of them. A comparison between the values of model parameters of solutions with BSA and without BSA allowed to conclude that the main effect of BSA is the formation of strongly bound hydration shells in the immediate proximity to the protein molecule. At the same time, the structure of more distant layers of the hydration shells is destroyed, with an increased formation of free water molecules. Some differences are observed in the effect of different BSA conformations on the aqueous phase of solution. The proposed approach can be generalized and applied for studying of a wide class of biological macromolecules in aqueous solutions.